Life Cycle Testing of Hermetic Compressors With Alternatives to CFC-12 - Sukumar Devotta; Nitin N Sawant; Shailesh N Joshi (Mesin, 1999)
Life cycle tests of hermetic compressors were conducted using a specially designed test rig that employs a gas cycle. They were conducted at an ambient temperature of 50